2010
DOI: 10.1021/jm9018542
|View full text |Cite
|
Sign up to set email alerts
|

Structure−Activity Relationship of (N)-Methanocarba Phosphonate Analogues of 5′-AMP as Cardioprotective Agents Acting Through a Cardiac P2X Receptor

Abstract: P2X receptor activation protects in heart failure models. MRS2339 3, a 2-chloro-AMP derivative containing a (N)-methanocarba (bicyclo[3.1.0]hexane) system, activates this cardioprotective channel. Michaelis-Arbuzov and Wittig reactions provided phosphonate analogues of 3, expected to be stable in vivo due to the C-P bond. After chronic administration via a mini-osmotic pump (Alzet), some analogues significantly increased intact heart contractile function in calsequestrinoverexpressing mice (genetic model of he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 36 publications
0
57
0
Order By: Relevance
“…We found that a non-hydrolyzable phosphonate analog of AMP could activate hA 1 R. Interestingly, other ectonucleotidase-resistant phosphonate analogs of AMP reportedly activate P2X receptors and have cardioprotective activity in vivo (47,48). Although it was suggested that the cardioprotective effects of these AMP analogs were due to P2X activation, P2X involvement was never directly tested in vivo with antagonists or knock-out mice.…”
Section: Discussionmentioning
confidence: 97%
“…We found that a non-hydrolyzable phosphonate analog of AMP could activate hA 1 R. Interestingly, other ectonucleotidase-resistant phosphonate analogs of AMP reportedly activate P2X receptors and have cardioprotective activity in vivo (47,48). Although it was suggested that the cardioprotective effects of these AMP analogs were due to P2X activation, P2X involvement was never directly tested in vivo with antagonists or knock-out mice.…”
Section: Discussionmentioning
confidence: 97%
“…P2X6R mRNA was reported to be upregulated in left myocardium of patients with CHF [480]. P2XR activation protected the heart in heart failure models [481,482]. A beneficial effect of MRS2339, a P2XR agonist in heart failure was demonstrated; it was identical to that produced by cardiac myocyte-specific over-expression of the P2X4R [483].…”
Section: Pathophysiology and Therapeutic Potentialmentioning
confidence: 99%
“…An initial Mitsunobu base coupling reaction of previously reported alcohol 15 22 using triphenylphosphine, diisopropyl azodicarboxylate and 3- N -benzoyluracil 23 followed by a debenzoylation using 6 N NH 3 /MeOH gave phosphonate diester 16 in 24% overall yield. Simultaneous deprotection of the phosphonate diester and the 2’,3’- O -isopropylidene group using freshly opened iodotrimethylsilane 24 afforded target phosphonate 17 .…”
Section: Resultsmentioning
confidence: 99%
“…After stirring for 40 min, a solution of compound 15 22 (85 mg, 0.23 mmol) in anhydrous THF (3 mL) was added to the mixture. After stirring for 36 h, the reaction mixture was evaporated to dryness.…”
Section: Methodsmentioning
confidence: 99%